Hubungan Tingkat Komunikasi Orang Tua Dengan Akhlak Anak di SD Negeri Gonilan 01 Kecamatan Kartasura Kabupaten Sukoharjo Tahun Pelajaran 2014/2015 - Sidiq, Wakhid Umar, Drs. Zaenal Abidin, M.Pd, Drs. Arief Wibowo, M.Ag (2015)
Children often feel uncomfortable to communicate with their parents because their parents do not understand the child's activities. This leads to communication between parents and children as substandard, causing a lack of love of parents to children. The absence of spare time parents to accompany the child's activities because parents are busy working also lead to the closing of the communication between parents and children. Though communication is affection. The objective of this study is to determine and describe communication and morals of parents of children in elementary school Gonilan 01 District Kartasura Sukoharjo. It also know the relationship between parent communication with the morals of a child in elementary school Gonilan 01 District Kartasura Sukoharjo. This research is quantitative with correlative analysis is housed in the District 01 Elementary School Gonilan Kartasura Sukoharjo. A population of 114 with a sample of 40 students of grade IV, V, and VI. Sample collection technique with purposive sampling. Methods of data analysis using product moment kolelasi test. Based on research that (1) the communication parents have an average of 69,98. Parent communication established with the child in a category is to reach 60%. (2) Morals children have an average of 61,05. Morals child shows in a category is to reach 70%. (3) There is a communication relationship of parents with children in elementary school morals Gonilan 01 District Kartasura Sukoharjo. It is based on the value of rXY = 0,502 greater rtabel = 0,312. The amount of communication relationship of parent to child morality was 25,2%, thus indicating that the communication relationships of parents of children in elementary school morals Gonilan 01 District Kartasura Sukoharjo amounted to 25,2% while the remaining 74,8% influenced by other variables beyond this research model.